DEVELOPMENT OF SNAKE-AND-LADDER AND LITERARY MONOPOLY LEARNING MEDIA BASED ON THE KUTAI MALAY LANGUAGE TO ENHANCE LINGUISTIC LITERACY OF STUDENTS WITH DISABILITIES - Vidia Fatmawati; Wahyu Widyatmoko (International Journal of Cultural and Social Science, 2026)
The preservation of regional languages faces serious challenges in the era of modernization, particularly for students with disabilities, who are still rarely the focus of regional language revitalization programs. This study aims to develop educational game-based learning media in the form of Snake and Ladder and Literary Monopoly games and to examine their effectiveness in improving the linguistic literacy of students with disabilities. The study employs a Research and Development (R&D) approach, encompassing stages of media design, limited implementation, and evaluation of learning outcomes. The research subjects were 11 junior high school–level students from a Special School (Sekolah Luar Biasa/SLB) in Samarinda City. Data were collected through observation, pre-tests and post-tests, and activity documentation. The results indicate an improvement in students’ understanding of Kutai Malay vocabulary and culture following the use of the learning media. The Snake and Ladder and Literary Monopoly media were found to be adaptive, engaging, and effective as linguistic learning tools for students with disabilities. This study recommends further development of game-based learning media as an inclusive strategy for regional language revitalization.